2009
DOI: 10.1086/595296
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Phenotypic Susceptibility Analyses for Nonthymidine Nucleoside Analogues Conferred by K65R or M184V in Mixtures with Wild-Type HIV-1

Abstract: Thymidine-sparing triple-nucleoside regimens have exhibited poor virologic response despite apparent phenotypic susceptibility to 2 of 3 regimen components at early time points. Phenotypic resistance masking by wild-type virus may explain this discrepancy.Consistent with this notion were (1) the presence of low level nucleoside reverse-transcriptase inhibitor-resistant human immunodeficiency virus in subjects receiving failing first-line regimens consisting of tenofovir (TDF), abacavir (ABC), and lamivudine (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…These findings underscore the limitation of stand-alone phenotypic susceptibility results and emphasize the importance of complementary and/or more sensitive genotyping techniques when evaluating for resistance [13]. In addition, these data further suggest that the impact of drug resistance mutations on therapy is multi-factorial and should take into account the proportion of the variant present, the mutational load, and the specific mutation present [10].…”
Section: Discussionmentioning
confidence: 68%
“…These findings underscore the limitation of stand-alone phenotypic susceptibility results and emphasize the importance of complementary and/or more sensitive genotyping techniques when evaluating for resistance [13]. In addition, these data further suggest that the impact of drug resistance mutations on therapy is multi-factorial and should take into account the proportion of the variant present, the mutational load, and the specific mutation present [10].…”
Section: Discussionmentioning
confidence: 68%
“…M184V was detected as the main mutation in most patients failing this regimen. It has been suggested that failure may have been attributable to viruses with K65R in addition EFV NVP ETV DRV NFV SQV LPV ATV APV IDV TPV RAL EVG ENF M41L K65R M41L T215Y WT WT WT WT WT WT WT WT T215Y WT M184V K65R M184V WT K65R M184V K65R M184V K103N WT Y181C G190S K103N Y181C Y181I G190S K101P Y181C Y181I I50V I54L I84V D30N L90M WT WT WT WT WT WT WT WT WT L90M G48V V32I I47A I47V V82A V82T V82F I50L I84V N88S I50V I84V M46I I84V M46L V82T V82F I84V V82T L33F G36D N42T Q40H V38A N43D Y143C Y143H G140S N155H Q148H Y143R Q148K Q148R WT N155H Q148H Q148K Q148R V82F K65R NRTI NNRTI PI InSTI FI to M184V (51,52). In many failing patients, however, this double mutant was not detected.…”
Section: Analysis Of Resistance Mutations Using Primary Cells Vs Tramentioning
confidence: 99%
“…The mechanism underlying the increased emergence of K65R and the unanticipated interaction between TDF + ABC and TDF + ddI, remain unclear [28–33]. Poor virological suppression could not be directly associated with either circulating drug levels or intracellular NRTI triphosphate levels [28].…”
Section: Barrier To K65r Selection Is Dependent On Nrti and Nnrti Regimensmentioning
confidence: 99%
“…Poor virological suppression could not be directly associated with either circulating drug levels or intracellular NRTI triphosphate levels [28]. Virological failure was initially associated with the rapid emergence of M184V and K65R on separate viral genomes [28–33]. …”
Section: Barrier To K65r Selection Is Dependent On Nrti and Nnrti Regimensmentioning
confidence: 99%
See 1 more Smart Citation